DAMPAK PARIWISATA TERHADAP ALIH FUNGSI LAHAN DI DESA TIBUBENENG KECAMATAN KUTA UTARA KABUPATEN BADUNG (STUDI SOSIAL-BUDAYA) - Agus Dipayana; I Nyoman Sunarta (JURNAL DESTINASI PARIWISATA, 2015)
ABSTRACT Tibubeneng is a village located in North Kuta district, Badung Regency as Central Badung Development Region which has a policy of maintaining Central Badung as agricultural areas in the broad sense and prevent the conversion of paddy fields. The question research of this research is about the impact of tourism on Land conversion. The selecting of Tibubeneng village as research location because the village of Tibubeneng is in the middle of the Badung region as an agriculture area, the nature and culture as the spirit of Tibubeneng village tourism, the village of Tibubeneng affected by the construction of accommodation facilities. The types of data in this research are the qualitative and quantitative data sourcing from the primary and secondary data. The data of this research is collected by interviews and the library research. The informant determining of this research to be started with determining the first informant and the key informant. The technique data analysis of this research is the qualitative descriptive analysis. According to research result in the village of Tibubeneng got by a the following result of development of tourism have an impact on increasing the agricultural land conversion, the land use change is impacted on the socio-cultural changes as well. According to the discussion , there are some suggestions that are needing of the role of government in monitoring and enforcing the regulations related to land use, and the community to change their profit-oriented mindset.